The Role of Scholarships in Shaping Student Consumption and Well-Being in Tanjungpinang - Rizki Fadhel Dwipananda; Ika Menarianti; M. Tasnim; Willa Fatika Sari; Anisa Laili Ramadani (Management Institute Faculty of Economics Universitas Andalas, 2026)
This study aims to analyze the influence of scholarships on the consumption patterns and financial well-being of students in Tanjungpinang City. The central problem motivating this research is the observed variation in consumption behavior and financial conditions among scholarship recipients, along with concerns that scholarship funds are not always utilized in an optimal and purposeful manner. This study employs a quantitative approach with an explanatory research design. Data were collected from two sources: primary data gathered through questionnaires distributed to 82 scholarship recipients, and secondary data comprising relevant previously published journal articles. Data analysis was conducted using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method with the assistance of SmartPLS software. The findings reveal that scholarships exert a positive and statistically significant impact on both student consumption patterns and student financial well-being. These results indicate that scholarships play a meaningful role in helping students allocate their expenditures in a more structured and purposeful manner, while also enhancing their perception of financial well-being throughout their period of study. This research is expected to provide empirical contributions to the development of student financial scholarship program managers in formulating more effective and sustainable scholarship policies.